4th-Century Orations on Farming: The Case of Themistius and Libanius - Kosznicki, Michał (Studia Ceranea, 2024)
The paper analyses two rhetorical texts from the 4th century – one by Themistius, found in the corpus of his so-called private speeches, titled Should one engage in agriculture (Θέσις εἰ γεωργητέον), and another by Libanius included in his collection of progymnasmata Praise of Agriculture (Ἐγκώμιον γεωργίας). An analysis of the two encomia shows great convergence in terms of the motifs and topoi used, e.g., in reference to the deities who take care of agriculture, praise of those who cultivate the land, emphasising their physical and spiritual qualities, the usefulness of their work for others. The purpose of the creation of the two works was different. While the purpose of Libanius’ encomium was didactic, Themistius’ piece was addressed to a mature audience and was probably part of some ongoing public discourse.